(untitled) (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2010)
The paper focuses on ill health and the issue of morality against the backdrop of the sick role - a functionalist approach to ill health initiated by Talcott Parsons. A fundamental reality is that being ill, is an unpleasant experience and has disruptive impacts on a group or society. What the ill person needs most is not blame but supportive interaction with family members and assistance from medical experts for him to get better. But more often than not, rather than gets the support, the gatekeepers of the sick role model morally evaluate ill health, thus, making the sick person blameworthy by attributing his/her ill health to moral failings and irresponsible lifestyle. The paper argues that moral evaluation of people with ill health or victim blaming ideology invalidates the sick role model. This serve as a legitimization of the denial of the rights and obligations of the sick person as stipulated by the sick role principle. The implication is that the individual is abandoned at the mercy of illness while its disruptive effect on the group or society prevails. The paper suggests re socialisation programme for the gatekeeper of the sick role as a way out of the crisis of moral evaluation of ill health